The Changing Distribution of Teacher Qualifications Across Schools: A Statewide Perspective Post-NCLB - Karen J. DeAngelis; Bradford R. White; Jennifer B. Presley (Arizona State University, 2010)
A number of recent policy initiatives, including NCLB's highly qualified teacher provisions, have sought to improve the qualifications of teachers and their distribution across schools. Little is known, however, about the impact of these policies. In this study, we use population data on teachers and schools in Illinois to examine changes in the level and distribution of teacher qualifications from 2001 to 2006. We find that schools in Chicago, especially those serving the highest percentages of low-income and minority students, experienced the greatest improvements in teacher qualifications during the period. In addition, high-poverty schools in most other locales in the state registered small to moderate improvements, which narrowed the gap in teacher qualifications between high- and low-poverty schools across Illinois. Improvements in the certification status of experienced teachers and the recruitment of new teachers with stronger academic qualifications both contributed to these gains. The results reveal a tradeoff for disadvantaged schools seeking to improve both teacher qualifications and teacher experience levels, thereby calling into question the near-term feasibility of NCLB provisions that aim to simultaneously eliminate inequities across schools in both.